2016
DOI: 10.1177/0954407016677435
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the instability mechanisms in a turbocharger centrifugal compressor with a vaneless diffuser by means of unsteady simulations

Abstract: The stable-flow range of a compressor is predominantly limited by surge and stall. In this paper, an unsteady simulation method was employed to investigate the instability mechanisms of a high-speed turbocharger centrifugal compressor with a vaneless diffuser. In comparison with the variation in the pressure obtained by dynamic experiments on the same compressor, unsteady simulations show a great accuracy in representing the stall behaviour. The predicted frequency of the rotating stall is 22.5% of the rotor f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…The maximum aspect ratio of cells is less than 900. Some researchers 6,14,15 reported that for a centrifugal compressor of this sort, about 7 million grid points are sufficient for a RANS simulation, thus supporting the effectiveness of the 20 million.…”
Section: Computational Meshmentioning
confidence: 97%
“…The maximum aspect ratio of cells is less than 900. Some researchers 6,14,15 reported that for a centrifugal compressor of this sort, about 7 million grid points are sufficient for a RANS simulation, thus supporting the effectiveness of the 20 million.…”
Section: Computational Meshmentioning
confidence: 97%
“…The generation mechanism for the rotating stall and surge of a centrifugal compressor was analyzed by Sundström et al [6]. In addition, several researchers have analyzed the mechanism with a variable vaned diffuser [7] and with a vaneless diffuser [8], and the acoustic signature [9] has been studied as well.…”
Section: Introductionmentioning
confidence: 99%
“…However, as an important component of turbocharger, the stable-flow range of a compressor is predominantly limited by surge and stall, which seriously limits the performance of turbocharger. 5 The centrifugal compressor consists mainly of the impeller, diffuser, and volute. As an asymmetric geometry component, the volute leads to the formation of a circumferentially non-uniform flow field in the compressor and seriously affects the performance and stability of the compressor.…”
Section: Introductionmentioning
confidence: 99%